The Metamorphosis of Aliens into Political Agents - Repetto, Elettra (Phenomenology and Mind, 2019)
Considering being political not as a status, but rather as an act that demands both capacity and action as its necessary conditions, I see being a political agent not as a permanent condition, but rather in a twofold dimension of potentiality and actuality. Moreover, I contend that the right to vote is not a necessary, nor a sufficient condition for being a political actor, although such a right can enhance our possibilities of having a say, augmenting one’s degree of political agency. This means that those individuals who are deprived of the right to vote, undocumented migrants in particular, can nonetheless be political agents in the polity. Indeed, notwithstanding the importance attached to the right to vote and to citizenship as fundamental for political participation, I claim that undocumented migrants are political although lacking the legal voting means of participation. Although much of the debate around migrants’ political participation has centred around the extension of the right to vote to migrants, there are in fact other rights that require attention. Moreover, even if we consider the right to vote as essential to protect people from abuses granting them a say within the polity, the arguments that have been proposed fail when it comes to recognize the rights and the political agency of undocumented migrants. In my understanding, migrants become political agents by their very same acting in the city, deserving to be heard and let free to express themselves in voicing their claims as subjects of justice, autonomous individuals, final units of our moral concern.